Potential for improving vehicle fuel efficiency and reducing the environmental pollution via fuel ionization - Al Ali, Yousif; Hrairi, Meftah; Al Kattan, Ibrahim (Center for Environmental and Energy Research and Studies, 2012)
In order to reduce the level of atmospheric pollution caused by vehicle engine emissions, application of a novel technique based on fuel magnetization has been tested in this study aiming at improving fuel efficiency and reducing the rate of gas emissions into the environment. Two experiments were conducted, each using a different type of magnetic device. The first type of magnetic device is installed within the fuel tank and the second is installed onto the fuel line. Each experiment was performed on ten separate vehicles from the Dubai Taxi Corporation fleet.When compared to the baseline data, reductions of 70 % for both hydrocarbon and carbon monoxide emissions, and 68 % for oxides of nitrogen were recorded. Results also demonstrated an average fuel consumption reduction of 18 %. These results clearly indicate that the introduction of magnetic field within the fuel supply of engine enhances the combustion process, thereby economizing fuel consumption and reducing the environmentally harmful emissions.